Wasser als kritischer Faktor der Ernährungssicherung.: Über die Bedeutung eines essentiellen Lebensmittels - Herbers, Hiltrud (ERDKUNDE, 1999)
It is commonly accepted among geographers that water as a means of irrigation plays a crucial role for the food supply of the growing world population. By contrast, the immediate impact of water on the food and nutrition security of the people in developing countries finds less attention within the geographical debate on water questions and nutritional problems. Due to the use of contaminated water for drinking and other purposes, many pathological germs enter the human organism, either orally or through the skin, and cause various infectious diseases. Undernourished individuals are particularly vulnerable because their immune system is weakened. An illness usually depresses appetite, hence food intake decreases during this period. At the same time the disease leads to a higher demand of nutrients caused by malabsorption and nutrient losses. The deficient demand, in turn, results in further deterioration of the anthropometric status of the person concerned, which then negatively affects the individual’s immunological resistance. Thus, there is a strong interdependence between infectious diseases and undernutrition. Both the insufficient quality and lack of drinking and other water perpetuates this vicious circle. Water is therefore a critical factor for nutritional security. Since people with a deficient health and nutritional status cannot make full use of their physical and mental abilities, social and economic disadvantages for individuals as well as for the whole society might be the result. Consequently, the inadequate water supply is also a major obstacle for enhanced development in Third World countries. The following paper contributes to the geographical research on nutritional security and development. It analyses the interdependence outlined above by considering findings of a study in Northern Pakistan.